Standardised inventories of spiders (Arachnida, Araneae) on touristic trails of the native forests of the Azores (Portugal) - Carvalho, Rui (2021)
In the Azores, as in many other temperate, semi-tropical and tropical islands, historical patterns of habitat loss have typically resulted in lowland clearance, meaning that the last remnants of the pre-human pristine forest that covered the major parts of oceanic islands are in the mountain areas (Gaspar et al. 2011). The communities of these mountain forests are of critical importance for the protection of current island biodiversity since they are home to many Azorean endemic species (Borges et al. 2017, Borges et al. 2018, Malumbres-Olarte et al. 2019) and provide a variety of ecosystem services (e.g. water storage, erosion control, pollination, pest-control, food supply, recreation and tourism), contributing to the local economy and welfare (Fernandez-Palacios et al. 2017). The recent increase in recreational tourist activities in native habitats of the Azores (SREA 2018) raises concerns about the use of trails being a threat to the already imperilled native forest biodiversity. Hiking trails in particular have been found to be promoting the spread of invasive plants (Barros and Pickering 2014), which may cause adverse cascading effects on arthropods. The spider communities of the Azores are exceptionally well known due to ongoing inventorying and monitoring projects carried out since 1999 (Borges et al. 2016, Emerson et al. 2017, Malumbres-Olarte et al. 2019). The protocol used in NETBIOME ISLANDBIODIV and in this project is part of a long term monitoring proposal for oceanic islands (Borges et al. 2018).